2014
DOI: 10.1002/gepi.21868
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Markers Associated With Plasma Protein C Level in African Americans: The Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Protein C is an endogenous anticoagulant protein with anti-inflammatory properties. Single-nucleotide polymorphisms (SNPs) affect the levels of circulating protein C in European Americans. We performed a genome-wide association (GWA) scan of plasma protein C concentration with approximately 2.5 million SNPs in 2,701 African Americans in the Atherosclerosis Risk in Communities Study. Seventy-nine SNPs from the 20q11 and 2q14 regions reached the genome-wide significance threshold of 5 × 10−8. A missense variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Two of these regions (2q13-q14/ PROC and 20q11/ PROCR ) were the same as those identified by the previous GWAS of protein C with HapMap imputation in the ARIC Study 8 . In the 2q13-q14 region, the top SNP on the IBC Array was in the 3’UTR of MAP3K2 (rs423353; P=7.2×10 −11 ), while a low frequency variant in CYP27C1 (rs140608390) had the most significant association in the 1000G GWAS (p=6.7×10 −24 ).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Two of these regions (2q13-q14/ PROC and 20q11/ PROCR ) were the same as those identified by the previous GWAS of protein C with HapMap imputation in the ARIC Study 8 . In the 2q13-q14 region, the top SNP on the IBC Array was in the 3’UTR of MAP3K2 (rs423353; P=7.2×10 −11 ), while a low frequency variant in CYP27C1 (rs140608390) had the most significant association in the 1000G GWAS (p=6.7×10 −24 ).…”
Section: Resultssupporting
confidence: 62%
“…In European Americans, associations with common variants [minor allele frequency (MAF) > 0.05] were found in four genomic regions located near PROCR (protein C receptor), PROC, GCKR , and BAZ1B , with a possible second independent association found at EDEM2 , located close to PROCR . In African Americans, genome-wide significant associations were found at PROCR and PROC , but not at GCKR or BAZ1B 8 . Genome-wide association studies (GWAS) in French 5 and Spanish 9 populations have also identified significant associations in the PROCR region.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“… 55 57 However, some genetic studies identify potential single-nucleotide polymorphisms (SNPs) that may affect the level of circulating protein C in multiple groups, including increased levels of protein C in African Americans. 58 While FV Leiden mutation, which results in activated protein C resistance, is a well-characterized mechanism of thrombosis in Caucasian populations, direct changes in protein C, protein S, and thrombomodulin have been found in some African Americans (as described above). African Americans also have increased levels of lipoprotein (a), which is known to play a role in the development of atherosclerosis and the predisposition to thrombosis due to its similarity to plasminogen, as well as through platelet activation.…”
Section: Covid-19 Disease Trendsmentioning
confidence: 98%
“…More recently, a study of the African American subset of the ARIC cohort (N = 2701) reported associations in PROCR, PROC and an intergenic region near PROC that collectively explained ~14% of the variance in protein C levels. (42)…”
Section: A Survey Of Gwas Studies In Thrombosis and Hemostasismentioning
confidence: 99%